A lifetime’s adventure in extracellular K+ regulation: the Scottish connection - Brown, Angus M. (Springer, 2017)
In a career that has spanned 45 years and shows no signs of slowing down, Dr Bruce Ransom has devoted considerable time and energy to studying regulation of interstitial K+. When Bruce commenced his studies in 1969 virtually nothing was known of the functions of glial cells, but Bruce’s research contributed to the physiological assignation of function to mammalian astrocytes, namely interstitial K+ buffering. The experiments that I describe in this review concern the response of the membrane potential (Em) of in vivo cat cortical astrocytes to changes in [K+]o, an experimental manoeuvre that was achieved in two different ways. The first involved recording the Em of an astrocyte while the initial aCSF was switched to one with different K+, whereas in the second series of experiments the cortex was stimulated and the response of the astrocyte Em to the K+ released from neighbouring neurons was recorded. The astrocytes responded in a qualitatively predictable manner, but quantitatively the changes were not as predicted by the Nernst equation. Elevations in interstitial K+ are not sustained and K+ returns to baseline rapidly due to the buffering capacity of astrocytes, a phenomenon studied by Bruce, and his son Chris, published 27 years after Bruce’s initial publications. Thus, a lifetime spent investigating K+ buffering has seen enormous advances in glial research, from the time cells were identified as ‘presumed’ glial cells or ‘silent cells’, to the present day, where glial cells are recognised as contributing to every important physiological brain function.